Fiscal responsibility: What exactly does it mean? - Jan Kregel (Levy Economics Institute of Bard College, 2010)
The use of government fiscal stimulus to support the economy in the recent economic crisis has brought increases in government deficits and increased government debt. This has produced an interest in sustainable government debt and the role of deficits in the economy. This paper argues in favor of a concept of 'responsible' government policy, referring to positions held by Franklin and Marshall Professor Will Lyons. The idea is that government should be responsible to the needs and desires of its citizens, but that this should go beyond physical security and education, to economic security. Building on the fallacy of composition and misplaced concreteness, it suggests that in an integrated macro system an increased desire to save on the part of the private sector will be self-defeating unless the government acts in a responsible manner to support those desires. This can only be done by government dissaving via an expenditure deficit. The outstanding government debt simply represents the desires of the public to hold safe financial assets, and can only be unsustainable if the public's desires change. The government should always be responsive to these desires, and adjust its expenditure policy.
Keywords: E61; E62; H31; H62; 330; deficit spending; sustainable deficits; responsible fiscal policy; Will Lyons